The role of PPAR in fungal keratitis - Zhou, Hongyan; Zhang, Hong; Bi, Miaomiao; Zhang, Wensong (Frontiers in Immunology, 2024)
The treatment of fungal keratitis(FK) remains challenging due to delayed fungal detection and the limited effectiveness of antifungal drugs. Fungal infection can activate both innate and adaptive immune responses in the cornea. Fungi stimulate the production of oxidative stress-related biomarkers and mediate the infiltration of neutrophils, macrophages, and T cells. These cells can induce infiltration of cytokines, chemokines, and matrix metalloproteinases (MMPs), leading to corneal tissue damage and even corneal perforation. The signaling pathway regulates the expression of inflammatory cytokines in fungal keratitis. Immune inflammatory damage is the main mechanism of FK, and oxidative stress damage is also involved in this infection process. Peroxisome proliferator-activated receptor (PPAR) is a member of the nuclear hormone receptor superfamily, with different subtypes of PPAR a, PPAR β/δ, and PPARγ. PPARs play important roles in the antioxidant response, anti-inflammatory, lipid metabolism, neuroprotection, and immune regulation processes. PPAR γ can promote macrophage polarization and reduce oxidative stress damage by regulating ROS production. PPAR has made some progress in the treatment of eye diseases: PPARa agonists can inhibit diabetes keratopathy and corneal neuropathy. PPARa agonists inhibit early immature angiogenesis in corneal alkali burns and have potential therapeutic effects on inflammatory corneal angiogenesis. PPARs can control the progression of dry eye disease and improve the condition of meibomian gland dysfunction. Based on this, we explored the potential roles of PPARs in the treatment of FK.